Occlusal Interferences: How Can This Concept Influence The Clinical Practice? - Lima, Adriano Fonseca; Cavalcanti, Andrea Nóbrega; Marcondes Martins, Luis Roberto; Marchi, Giselle Maria (European Journal of Dentistry, 2010)
This brief review discusses the role of occlusal interferences on the development and progression of temporomandibular dysfunction (TMD) and postural disorders. The eligible literature is described and critically presented to demonstrate that occlusal interferences are an important factor in the risk of TMD. Several studies have demonstrated through their findings that the use of occlusal adjustments, whether or not associated with restorative procedures, might avoid the development of articular problems in vulnerable patients. The occlusal interferences caused by restorative procedures or orthodontic treatment can cause TMDs in susceptible patients, and occlusal adjustments can be an alternative in the treatment of these TMDs. (Eur J Dent 2010;4:487-491)
Keywords: Temporomandibular dysfunction; Occlusal interferences